2010
DOI: 10.1111/j.1439-0388.2010.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene expression and intramuscular fat content in pigs

Abstract: Seventy-two pigs of three genetic groups (Brazilian indigenous breed Piau, Commercial line and Crossbred) of both sexes were slaughtered at four live weights (30, 60, 90 and 120 kg). Intramuscular fat (IMF) content in Longissimus dorsi muscle of each animal was extracted and correlated with candidate gene mRNA expression (ATN1, EEF1A2, FABP3, LDLR, MGP, OBSCN, PDHB, TRDN and RYR1). Within slaughter weight of 120 kg, Piau and Crossbred pigs showed higher IMF content (p < 0.05) than commercial animals, with 2.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 21 publications
6
43
0
Order By: Relevance
“…Few studies have suggested that the association between the IMF content and tenderness might be deciphered by the fat cell expansion in the perimysium, which might open the muscle structure by forcing the muscle bundles apart (Wood, 1990). Recently, most of studies on IMF have focused on the mechanisms of lipogenesis (Morcuende et al, 2007;Zhao et al, 2009), and numerous candidate genes associated with IMF deposition had been identified (Cánovas et al, 2010;Serão et al, 2011;Tyra and Ropka-Molik, 2011), which may improve our ability to effectively enhance the IMF content in pork and other livestock.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have suggested that the association between the IMF content and tenderness might be deciphered by the fat cell expansion in the perimysium, which might open the muscle structure by forcing the muscle bundles apart (Wood, 1990). Recently, most of studies on IMF have focused on the mechanisms of lipogenesis (Morcuende et al, 2007;Zhao et al, 2009), and numerous candidate genes associated with IMF deposition had been identified (Cánovas et al, 2010;Serão et al, 2011;Tyra and Ropka-Molik, 2011), which may improve our ability to effectively enhance the IMF content in pork and other livestock.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome in humans is caused by heterozygous deletions of about 1.6 Mb, and one of the numerous symp- (Sasaki et al, 2006;Serao et al, 2011) 18 56 485 824-57 128 560 R PSMA2 negative correlation with male BMI (Sakamoto et al, 2009) toms in about 15 % of the cases is hypercalcemia (Cagle et al, 2004). Thus, at least one of the genes in this region must have an influence on blood calcium levels.…”
Section: Resultsmentioning
confidence: 99%
“…The decision about a possible candidate status was thus hindered. However, in 7 of the 10 remaining regions, possible candidate genes could be identified: WBSCR17 (International Mouse Phenotyping Consortium), SRSF7 (International Mouse Phenotyping Consortium), USP28 (Valero et al, 2001), NNMT (Trammell and Brenner, 2015), ZBED6 (Clark et al, 2015;Markljung et al, 2009), NMNAT2 (Hicks et al, 2012), ABHD6 (Thomas et al, 2013), PDHB (Sasaki et al, 2006;Serao et al, 2011) and PSMA2 (Sakamoto et al, 2009). These are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, local breeds such Piau, exhibits decreased growth rate and greater fat content (Serão et al, 2011) compared to commercial pig breeds.…”
Section: Introductionmentioning
confidence: 99%